A Software Quality Model Combining Demand and Delivery Perspectives to Ensure Quality in IT Implementations - Wei Xu; Klaus Greve; Marius Schlage; Justus Tillmann Holler; Jochen Hagen (International School for Social and Business Studies, 2023)
In this paper we describe a model which fosters the quality of the artefact within software development projects via defined quality gates. In combination with defined roles these quality gates facilitate communication and transparency regarding the progress within the project and of the software artefact in particular. The motivation for this paper have their origin in identified and confirmed challenges during software development projects which do not follow a defined quality control mechanism. We evaluate the quality model in relation to current software development projects in classical as well as agile environments, one of which we describe in this paper. The project setting includes multiple business departments, business IT, internal delivery IT and external delivery IT departments. It deals with the central procurement platform in the company.